Myocardial infarction and embolism: a rare combination associated with a poor prognosis (a clinical case) - O. L. Lyakhovich; O. V. Filyushin; S. S. Yakushin (Рациональная фармакотерапия в кардиологии)
The article describes a clinical case of a 44-year-old woman with almost simultaneous onset of massive pulmonary embolism (bilateral involvement) secondary to posterior tibial vein thrombosis with a floating thrombus, and embolic myocardial infarction caused by paradoxical embolism through an atrial septal defect. These events occurred against a background of severe anemia of unknown etiology. The management strategy initial primary percutaneous coronary intervention for type 2 myocardial infarction and thrombotic occlusion of the posterior interventricular artery with stent implantation, and subsequent thrombolytic therapy for pulmonary embolism. The article further discusses the complex issues of prescribing and adjusting antithrombotic therapy based on decisions by medical council, which led to significant clinical improvement by the time of the patient’s discharge.